2018
DOI: 10.1103/physreve.97.020202
|View full text |Cite
|
Sign up to set email alerts
|

Period doubling in period-one steady states

Abstract: Nonlinear classical dissipative systems present a rich phenomenology in their "route to chaos," including period doubling, i.e., the system evolves with a period which is twice that of the driving. However, typically the attractor of a periodically driven quantum open system evolves with a period which exactly matches that of the driving. Here, we analyze a periodically driven many-body open quantum system whose classical correspondent presents period doubling. We show that by studying the dynamical correlatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 31 publications
0
46
0
Order By: Relevance
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…A crystalline structure in time is related to the periodic dynamics of a system. It has been shown that periodically driven quantum many-body systems can spontaneously self-reorganize their motion and start moving with a period different from the period of the driving [12][13][14] (see also [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]). This kind of spontaneous formation of a new crystalline structure in time is dubbed discrete or Floquet time crystals and has been already realized experimentally [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The open nature is common to a vast class of modern experimental platforms in quantum science and technology, such as photonic systems [4], ultracold atoms [5-9], optomechanical systems [10][11][12][13] or superconducting circuits [14][15][16], for which driving and losses are omnipresent. Open quantum systems also display emergent physics, in particular dissipative phase transitions and topological phases [40][41][42][43][44][45].Several studies have highlighted the possibility for a continuous-wave driven-dissipative quantum system to reach a non-stationary state in the long time limit in which undamped oscillations arise spontaneously [46][47][48][49][50][51][52]. This phenomenon has been dubbed as boundary or dissipative time crystal (DTC), in analogy with the time crystals in some Hamiltonian systems [53].…”
mentioning
confidence: 99%
“…For meso-and nanoscopic systems, such a steady state can still exhibit significant fluctuations [1]. Beyond the quantum domain, in which such systems have found considerable attention recently, see, e.g., [2][3][4][5][6][7] and refs. therein, colloidal systems provide a major paradigm [8].…”
mentioning
confidence: 99%